Can femoral access bleeding outcomes be improved?. Issue 3 (15th February 2015) - Hillegass, William B.; Brott, Brigitta C.
Key Points In the absence of randomized trials, the role of vascular closure devices as a bleeding avoidance strategy compared to manual compression in ST‐elevation myocardial infarction (STEMI) patients undergoing percutaneous coronary intervention remains poorly defined. Vascular closure devices in a propensity adjusted observational analysis were associated with one less major bleed for every 32 STEMI patients closed [95% CI: 20, 77]. Adjuncts to technique coupled with vascular closure devices may have the potential to improve femoral access safety to the level of radial access.